Eating behavior affects cardio-metabolic risk in high school teenagers in a developing country (Medical Journal of Indonesia, 2020)
BACKGROUND Modernization negatively changes lifestyle, characterized by excessive eating and reduced energy consumption, and concurrently increases the cardiometabolic risk. This study was aimed to evaluate the association between eating behavior and cardio-metabolic risk factors including body mass index (BMI) in percentile, blood pressure (BP) in percentile, waist circumference, and heart rate in total subjects and gender sub-groups. METHODS This analytical cross-sectional study was done from July to November 2018. High schools in four provinces of Indonesia and students were selected using purposive sampling. Subjects’ profiles were collected from interview and cardio-metabolic parameters were measured at the study sites. Data were analyzed with chi-square and independent t-test. RESULTS Subjects who were overweight/obese and had high BP accounted for 27.1% and 9.3–12.0% of the total subjects (n = 768), respectively. Subjects who having breakfast tended to have lower BMI (p = 0.006), and the lower consumption of western meals had lower heart rate (p = 0.02). Male subjects had more meal frequency and had less quantity of snacks than female subjects (p<0.001). Male subjects with routine intake of vegetables had low heart rate (p = 0.03). Female subjects with routine breakfast had better BMI (p<0.001), and lower diastolic BP (p = 0.004) and waist circumference (p = 0.02), whereas those who consumed Western meals had higher heart rate (p = 0.046) and waist circumference (p = 0.001). CONCLUSIONS Eating behaviors are likely to affect cardio-metabolic risk factors, and the effects vary within gender groups.